Analisis Tren Produksi dan Produktivitas Tebu pada Pabrik Gula Prajekan Kabupaten Bondowoso - Mayangsari, Andina; Sholikhah, Ummi; Rahman, Moh. Syaoki; Mawaddah, Nur (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
The national sugar industry in Indonesia continues to face challenges in meeting domestic demand, making the improvement of sugarcane production performance increasingly important. East Java Province is the main center of national sugar production, one of which is supported by Prajekan Sugar Factory in Bondowoso Regency. This study aims to analyze the trends of sugarcane land area, sugarcane production, and sugarcane productivity at Prajekan Sugar Factory during the period 2010–2024, as well as to project their development for the next five years. This research employed a quantitative descriptive approach using trend analysis with a simple linear regression (least square method). The data used consisted of annual time series data on sugarcane land area, sugarcane production, and sugarcane productivity obtained from Prajekan Sugar Factory. The results indicate that sugarcane production fluctuated over time but showed an increasing trend, while the sugarcane land area tended to decline. Meanwhile, sugarcane productivity exhibited an increasing trend during the observation period. The five-year projection suggests that future increases in sugarcane production are more strongly driven by improvements in productivity rather than land expansion. These findings imply that sugarcane development strategies at Prajekan Sugar Factory should focus on intensification through productivity enhancement and efficient land utilization in a sustainable manner.